Relevance of Copenhagen Criteria in Actual Accession: Principles, Methods and Shortcomings of EU Pre-accession Evaluation - Veebel, Viljar (Studies of Transition States and Societies, 2011)
This paper will analyse the transparency, impartiality and objectiveness of the European Union’s (EU) preaccession assessment procedure. The principal aim is to test and analyse whether the EU follows oﬃ cial and objective criteria in its progress reports or if is it dominated by institutional and national interests. The central questions of the paper are: What were the main motivators of the EU’s independent closed assessment system for the pre-accession process and what inﬂ uence did this have on the accession process during the years 2004–2006?To answer these questions, the paper will compare the European Commission’s (Commission) progress reports on selected candidate countries with the assessments of six other respected research centres: the International Monetary Fund, the World Bank, Freedom House, the Bertelsmann Foundation, Transparency International, Fraser Institute and the Heritage Foundation. If the evaluation results of the EU diﬀ er signiﬁ cantly or systematically from the calculated average of the other evaluators, then there is a need to analyse the methods, logic and motivation of the European Commission during the preaccession evaluation, as there is a possibility of subjectivity and politicised evaluation.This analysis covers the main areas of the Copenhagen Criteria. The test cases will be pre-accession progress assessments of Bulgaria, Croatia, FYROM and Romania in 2004–2006. Test areas will consist of: Governance eﬃ ciency; Existence and quality of rule of law; Level of corruption and eﬃ ciency of anticorruption activities; Eﬃ ciency of legal system, and Economic liberties and freedoms.